Outcomes of Extended Curettage with and without Bone Allograft for Grade II Giant Cell Tumors around the Knee. A Retrospective Comparative Study - Badaruddin Sahito; Sheikh Muhammad Ebad Ali; Bushra Majid; Muhammad Soughat Katto; Asif Jatoi; Syed Jahanzeb (Revista Brasileira de Ortopedia, 2023)
Abstract Objective This is the first study to establish the utility of extended curettage with or without bone allograft for Grade II giant cell tumors GCTs around the knee joint with the aim of exploring postoperative functional outcomes. Methods We retrospectively reviewed 25 cases of Campanacci grade II GCTs undergoing extended curettage between January 2014 and December 2019. The participants were divided into two groups: one group of 12 patients underwent extended curettage with bone allograft and bone cement, while the other group of 13 patients underwent extended curettage with bone cement only. Quality of life was assessed by the Revised Musculoskeletal Tumor Society Score and by the Knee score of the Knee Society; recurrence and complications were assessed for each cohort at the last follow-up. The Fisher test and two-sample t-tests were used to compare the categorical and continuous outcomes, respectively. Results The mean age was 28.09 (7.44) years old, with 10 (40%) males and 15 females (60%). The distal femur and the proximal tibia were involved in 13 (52%) and in 12 (48%) patients, respectively. There was no significant difference in the musculoskeletal tumor society score (25.75 versus 27.41; p= 0.178), in the knee society score (78.67 versus 81.46; p= 0.33), recurrence (0 versus 0%; p= 1), and complications (25 versus 7.69%; p= 0.21). Conclusions Extended curettage with or without bone allograft have similar functional outcomes for the knee without any major difference in the incidence of recurrence and of complications for Grade II GCTs. However, surgical convenience and cost-effectiveness might favor the bone cement only, while long-term osteoarthritis prevention needs to be investigated to favor bone allograft.